Ohranjenost drevesne sestave in realizacija možnega poseka zmanjšujeta obseg sanitarnih sečenj v Sloveniji - Diaci, Jurij (Gozdarski vestnik, 2021)
The generally adopted standpoint is that we reduce the risks in forest management through close-to-nature management. There are good examples of management and indirect proofs confirming this standpoint, however, there is a lack of scientific studies confirming it based on quantitative analyses. In Slovenia, we confirmed positive links between the preserved tree structure, regular management, and fewer sanitary fellings. In a time of distinct environmental changes, it is reasonable to encourage regular forest management. Due to social and economic changes, abandoning the management will be even more distinct in the future. In addition to the role of the regular management for the wood processing chain supply, major stress will have to be given to the significance of the active management for adapting the forest to the environmental changes and forest health in the future.
Keywords: activation of forest management; aktiviranje gospodarjenja z gozdovi; bark beetles; forest health; podlubniki; possible harvest realization; realizacija možnega poseka; sestoji smreke; spruce stands; zdravje gozda